Comparison of Umbilical Artery Flow Velocity Waveforms with Fetal Perfusion Pressures in Ex Vivo Placenta Cotyledon [5P]. (May 2018) - Pino, Daniela; Bednov, Andrey; Carillo, Maira; Maguire, Christopher; Maher, James; Schlabritz-Lutsevich, Natalia
Abstract : INTRODUCTION: The spectral Doppler indices obtained during antenatal sonography are used to evaluate placental resistance in vivo because direct measurement of flow volume in utero is not easily attainable. Placental perfusion pressures obtained from an ex-vivo placental cotyledon can be calculated at standardized flow rates. We sought to compare the ex vivo pressures to in utero Doppler flow indices. METHODS: Dual perfused ex vivo human placenta cotyledons from 28 women delivered at 37-39 weeks (IRB #L-014) were cannulated. The inflow pressure (IFP) in the fetal artery at inflow velocity of 4.5 ml/min as well as cotyledon weight were recorded. The umbilical artery flow velocity waveform analysis from routine antenatal sonography was retrospectively collected in twelve women at a mean gestational age of 35.6 +2.5 weeks. The S/D ratio, RI, and PI were obtained. RESULTS: The IFP correlated negatively with the cotyledon weight (r=.0485, P=.009) The raw Doppler indices were not significantly correlated with placental or fetal weight, However, if the pressure controlled for cotyledon weight was compared to Doppler index controlled for placenta weight, there was a positive correlation between Doppler RI and placental perfusion pressure. (p=.0086). There was a weak negative correlation between IFP and estimated the fetal weight at the time of ultrasound. (r=.47, p=.06). CONCLUSION: Small placental vessels are responsible for the resistance calculated in the umbilical artery. In the dually perfused placenta, our study suggests that the pressure in the functional placental unit of a perfused cotyledon is correlated with the Doppler flow indices on antenatal ultrasound.